Reasons of startups’ failures in fundraising at Shark Tank in Vietnam - Lê Nguyễn Bình Minh (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2020)
After reviewing literature and theories on startup business and venture capital, this research analyzes 40/90 projects which fail to call for funding from investors at Shark tank Vietnam (a reality show on TV and Youtube channel). The result indicates 3 major factors which affect the investors’ decisions. This research aims to give recommendations to startups on getting ready for funding rounds as well as implications for startup training programs at Vietnam Universities and Colleges.